Open Source EEG Platform with Reconfigurable Features for Multiple-scenarios - López, Juan M.; González, Fabián; Bohórquez, Juan C.; Bohórquez, Jorge; Valderrama, Mario A; Segura Quijano, Fredy (Institute of Advanced Engineering and Science (IAES), 2018)
Electroencephalogram (EEG) acquisition systems are widely used as diagnostic and research tools. This document shows the implementation of a reconfigurable family of three affordable 8-channels, 24 bits of resolution, EEG acquisition systems intended for a wide variety of research purposes. The three devices offer a modular design and upgradability, permitting changes in the firmware and software. Due to the nature of the Analog FrontEnd (AFE) used, no high-pass analog filters were implemented, allowing the capture of very low frequency components. Two systems of the family, called “RF-Brain” and “Bluetooth-Brain”, were designed to be light and wireless, planned for experimentation where movement of the subject cannot be restricted. The sample rate in these systems can be configured up to 2000 samples per second (SPS) for the RF-Brain and 250 SPS for the BluetoothBrain when the 8 channels are used. If fewer channels are required, the sampling frequency can be higher (up to 4 kSPS or 2 kSPS for 1 channel for RF-Brain and Bluetooth-Brain respectively). The third system, named “USBBrain”, is a wired device designed for purposes requiring high sampling frequency acquisition and general purpose ports, with sampling rates up to 4 kSPS.

Los sistemas de adquisición de electroencefalograma (EEG) se utilizan ampliamente como herramientas de diagnóstico e investigación. Este documento muestra la implementación de un Familia reconfigurable de tres asequibles canales de 8, 24 bits de resolución, Sistemas de adquisición de EEG destinados a una amplia variedad de fines de investigación. Los tres dispositivos ofrecen un diseño modular y capacidad de actualización, lo que permite cambios en el firmware y software. Debido a la naturaleza del FrontEnd analógico (AFE) utilizado, no se implementaron filtros analógicos de paso alto, lo que permitió Captura de componentes de muy baja frecuencia. Dos sistemas de la familia, llamados “RF-Brain” y “Bluetooth-Brain”, fueron diseñados para ser livianos y inalámbrico, planeado para experimentación donde el movimiento del sujeto no puede estar restringido. La frecuencia de muestreo en estos sistemas se puede configurar hasta 2000 muestras por segundo (SPS) para RF-Brain y 250 SPS para BluetoothBrain cuando se utilizan los 8 canales. Si se requieren menos canales, el La frecuencia de muestreo puede ser mayor (hasta 4 kSPS o 2 kSPS para 1 canal para RF-Brain y Bluetooth-Brain respectivamente). El tercer sistema, denominado “USBBrain”, es un dispositivo cableado diseñado para fines que requieren una alta capacidad de muestreo. Adquisición de frecuencia y puertos de uso general, con tasas de muestreo de hasta 4 kSPS
Keywords: Electrodiagnóstico; Electrodiagnosis; Actividad nerviosa superior; Higher nervous activity; Generadores de impulsos; Pulse generators; Generadores de señales; Signal generators; Biorretroalimentación; Biofeedback; Interfaz cerebro-computadora (ICC); Brain-Computer Interface (BCI); Electroencefalografía (EEG); Electroencephalography (EEG); Neurofisiología; Neurophysiology; Instrumentos portátiles; Portable instruments